Correcting misperceptions about support for social distancing to combat COVID-19 - Allen IV, James; Mahumane, Arlete; Riddell IV, James; Rosenblat, Tanya; Yang, Dean; Yu, Hang (University of Chicago Press, 2024)
Can informing people of high community support for social distancing encourage them to do more of it? We randomly assigned a treatment to correct individuals’ underestimates of community support for social distancing. In theory, informing people that more neighbors support social distancing than expected encourages free riding and lowers the perceived benefits from social distancing. At the same time, the treatment induces people to revise their beliefs about the infectiousness of COVID-19 upward; this perceived-infectiousness effect and the norm-adherence effect increase the perceived benefits from social distancing. We estimate the effects on social distancing, which are measured by using a combination of self-reports and reports of others. While experts surveyed in advance expected the treatment to increase social distancing, we find that its average effect is close to zero and significantly lower than expert predictions. However, the treatment’s effect is heterogeneous as predicted by theory: it decreases social distancing where current COVID-19 cases are low (where free riding dominates) but increases it where cases are high (where the perceived-infectiousness effect dominates). These findings highlight that correction of misperceptions may have heterogeneous effects depending on disease prevalence.